NAP1L5 Promotes Nucleolar Hypertrophy and Is Required for Translation Activation During Cardiomyocyte Hypertrophy - Guo, Ningning; Zheng, Di; Sun, Jiaxin; Lv, Jian; Wang, Shun; Fang, Yu; Zhao, Zhenyi; Zeng, Sai; Guo, Qiuxiao; Tong, Jingjing; Wang, Zhihua (Frontiers in Cardiovascular Medicine, 2021)
Pathological growth of cardiomyocytes during hypertrophy is characterized by excess protein synthesis; however, the regulatory mechanism remains largely unknown. Using a neonatal rat ventricular myocytes (NRVMs) model, here we find that the expression of nucleosome assembly protein 1 like 5 (Nap1l5) is upregulated in phenylephrine (PE)-induced hypertrophy. Knockdown of Nap1l5 expression by siRNA significantly blocks cell size enlargement and pathological gene induction after PE treatment. In contrast, Adenovirus-mediated Nap1l5 overexpression significantly aggravates the pro-hypertrophic effects of PE on NRVMs. RNA-seq analysis reveals that Nap1l5 knockdown reverses the pro-hypertrophic transcriptome reprogramming after PE treatment. Whereas, immune response is dominantly enriched in the upregulated genes, oxidative phosphorylation, cardiac muscle contraction and ribosome-related pathways are remarkably enriched in the down-regulated genes. Although Nap1l5-mediated gene regulation is correlated with PRC2 and PRC1, Nap1l5 does not directly alter the levels of global histone methylations at K4, K9, K27 or K36. However, puromycin incorporation assay shows that Nap1l5 is both necessary and sufficient to promote protein synthesis in cardiomyocyte hypertrophy. This is attributable to a direct regulation of nucleolus hypertrophy and subsequent ribosome assembly. Our findings demonstrate a previously unrecognized role of Nap1l5 in translation control during cardiac hypertrophy.